THE ROLE OF STUDENTS IN THE COMMUNITY AS A FORM OF SERVICE IN THE FIELD OF EDUCATION IN KAJHU VILLAGE, BAITUSSALAM DISTRICT, ACEH BESAR REGENCY - Maimun; Sufyan; Riyan Maulana; Adi Ahmad (CV. Naskah Aceh, 2024)
Community service carried out by students is a service to the community. Community service activities are an effort to educate the nation's life, so one of the activities that need to be carried out by students in the field of education is to carry out community service. To compile community service activity programs in the educational aspect, it is necessary to carry out counseling activities with the aim that students can carry out community service activities well and on target. This activity can be carried out well and produce several student activity programs in the field of Education, namely teaching Indonesian, teaching mathematics, teaching drawing, teaching reading the Qur'an, and helping teachers teach in PAUD. This activity targets elementary school students who also involve the village community, village officials, and parents of students in Kaju Village, Baitussalam District, Aceh Besar Regency.